EFFECT OF DIETARY INTAKE CONTAINING VITAMINS A, C AND E ON TUBERCULOSIS PATIENTS - Yasmin, Ratri; Zuhri , Fuad Minan (Universitas Airlangga, 2025)
Tuberculosis is a chronic infectious disease that is almost universally natural, caused by Mycobacterium tuberculosis. TB has a strong relationship with vitamins A, C, and E. This is due to the modulating action of these vitamins in the inflammatory process. Data was collected through literature review from electronic databases such as PubMed and SCOPUS. The keywords are